Nanopore arrays in a silicon membrane for parallel single-molecule detection: fabrication. (16th July 2015) - Schmidt, Torsten; Zhang, Miao; Sychugov, Ilya; Roxhed, Niclas; Linnros, Jan
Abstract: Solid state nanopores enable translocation and detection of single bio-molecules such as DNA in buffer solutions. Here, sub-10 nm nanopore arrays in silicon membranes were fabricated by using electron-beam lithography to define etch pits and by using a subsequent electrochemical etching step. This approach effectively decouples positioning of the pores and the control of their size, where the pore size essentially results from the anodizing current and time in the etching cell. Nanopores with diameters as small as 7 nm, fully penetrating 300 nm thick membranes, were obtained. The presented fabrication scheme to form large arrays of nanopores is attractive for parallel bio-molecule sensing and DNA sequencing using optical techniques. In particular the signal-to-noise ratio is improved compared to other alternatives such as nitride membranes suffering from a high-luminescence background.